Multiple irregularities and thrombus in a patient with COVID-19 presenting with ST-segment elevation myocardial infarction: a case report - Shah, Bhupesh; Shah, Harshal; Shah, Darshil (Journal of Ideas in Health, 2021)
Background: Multiple thrombi are likely to develop in Coronavirus Disease 2019 (COVID-19) patients. Hence, achieving successful outcomes following catheterization becomes quite challenging in such patients. Case presentation: We report a challenging case of a 36-year-old female with ST-Segment Elevation Myocardial Infarction (STEMI). Coronary angiography revealed multiple irregularities in the coronary tree as well as thrombi. Although computed tomography imaging of the thorax was normal, reverse transcription-polymerase chain reaction (RT-PCR) confirmed the diagnosis of COVID-19. The outcome was good TIMI flow after a successful Primary Angioplasty in Acute Myocardial Infarction (PAMI), and the patient was isolated and then switched to oral anticoagulants (clopidogrel) for dual antiplatelet therapy (DAPT) therapy. Conclusion: This case emphasizes the management of a COVID-19 patient for PAMI.